An investigation into the regulatory capacity of invariant natural killer T (iNKT) cells during the innate and adaptive immune response to influenza infection - McEwen-Smith, R (2014)
Influenza A virus (IAV) infection is a highly contagious respiratory disease, which can cause substantial morbidity and occasionally death. Invariant natural killer T (iNKT) cells, a subset of CD1d-restricted T lymphocytes, have been identified as important modulators of immunity, mediating both pro- and anti-inflammatory responses. We show that iNKTs play an important role for the generation of protective innate and adaptive immune responses to IAV, and enhance heterotypic immunity to influenza virus following vaccination with a novel pseudotyped virus, S-FLU, which lacks HA expression. iNKT-deficient mice (Jα18-/-) showed increased susceptibility and lung pathology following IAV infection, which correlated with an exaggerated accumulation of inflammatory monocytes and neutrophils in the lung. Consistent with these findings, we demonstrated in IAV-infected CD1d-/-:CD1d+/+ mixed bone marrow chimeric mice, that the lack of CD1d expression on myeloid cells purified from the lungs of IAV-infected mice significantly increased expression of genes linked to cell activation, survival and polarisation between pro- and antiinflammatory responses. We extended these results by examining the role of chemokine signalling during IAV infection, and identified a novel role for fractalkine (CX3CL1) and its receptor (CX3CR1) in innate immune cell recruitment. The use of CX3CR1-iNKT cell double knockout mice revealed that, although upregulated in Jα18-/- mice, CX3CR1-CX3CL1 signalling is not required for cell migration during exacerbated IAV-responses. Finally, we showed that iNKT-deficient mice displayed reduced longevity of peripheral IAVspecific CD8+ T cells following S-FLU vaccination, compared with wild-type mice. S-FLU vaccination protected mice following 5 day heterotypic challenge, however vaccinated mice exhibited reduced viral clearance, and importantly a significant reduction in IAV specific memory T cell response, suggesting a possible role of iNKT cells during T cell priming in modulating the lifespan of antigen-specific T cell responses. Although additional experiments are warranted, these results suggest that harnessing iNKT cells should be considered to modulate the innate and adaptive immune response to optimise heterotypic vaccine design and for therapeutic intervention against acute influenza infection.